Etika Global sebagai Fondasi Dialog Antaragama Menurut Perspektif Hans Kung - Martina Rosmaulina Marbun; Selvianti Dakhi; Yohanes Jok Pendopo Laoli; Ester Fosumange Laia; Junita Hulu; Agnes Monika Sarumaha; Seiring Lahoho (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This paper discusses the concept of global ethics put forward by Hans Küng as a universal moral framework in the face of the reality of a plural world. This study uses a qualitative approach with a literature study method to examine Küng's thoughts on global ethics, its basic principles, and its implications in social life and interreligious dialogue. The results of the study show that global ethics is a consensus of universal moral values that is not intended as a new religion, but as a common basis for all mankind in building a peaceful and just life. Principles such as humanity, non-violence, solidarity, honesty, and equality are the main cornerstones in building cross-cultural and religious relations. In addition, global ethics also encourages collective responsibility in maintaining social justice, human rights, and environmental sustainability. However, global ethics also faces criticism of its normative tendencies as well as the challenges of achieving universal consensus amid differences in values, cultures, and political interests. Therefore, the implementation of global ethics requires an inclusive, open, and sustainable dialogue. Thus, global ethics has strong relevance as the foundation of interreligious dialogue in creating sustainable global peace and harmony.